Using Digital Games to Teach History: A Design-Based Study - Çelik Türkan (Research on Education and Media)
The present study aims to examine prospective history teachers’ process of using digital games to design history lessons and delivering the designed lessons in virtual classrooms. The study employed a design-based research model and was conducted with 31 participants selected based on the criterion sampling method. Data were collected through design documents, interview forms, and video recordings and were analyzed using descriptive and content analysis techniques. During the process, participants were able to design history lessons with digital games and deliver the designed lessons in virtual classrooms. Analysis of participants’ views on the process led to the emergence of the following themes: “The Problems Emerging in the Process,” “The Pedagogical Effects of the Process,” “The Technological Effects of the Process,” “The Effects of the Process on Reflective Thinking,” “The Effects of the Process on Participants’ Thoughts about Virtual Learning Settings,” and “The Effects of the Process on Participants’ Thoughts about the Researcher.” The study results show that despite some problems with the use of technology, the process had a positive effect on the participants. In this regard, future studies may be recommended to focus on prospective teachers’ competencies in using technology effectively when teaching lessons in virtual learning environments.